MOTIF KORUPSI DALAM AL-QUR’AN PERSPEKTIF TINDAKAN SOSIAL - Siti Muwahidah (UIN Sunan Kalijaga Yogyakarta, 2020)
Corruption is one of the actions included in the category of extra-ordinary crime. A large number of this criminal activity has led many researchers to analyze the sources and causes from various aspects, including theological aspects. Qur'an, the main guide that governs all aspects of life, does not specifically mention this term. However, some terms in Qur'an have an equivalent meaning and characteristics with corruption. This research uses a thematic method to collect verses that have the same theme and uses the social action approach of Alfred Schutz. Through the thematic method, this research found a term mentioned in the Qur'an that has a meaning and character equivalent to corruption. These terms are scattered in several Surahs in the Qur'an, namely al-Ghulul contained in the Q.S. Ali Imran (3): 161; al-hirabah in Q.S. al-Maidah (5): 33; al-idla' in the Q.S. al-Baqarah (2): 188; al-suht in Q.S. al-Maidah (5): 42, 62 and 63; and the term al-khasr in the Q.S. al-Mutaffifin (83): 3. By analyzing word structure and its chronological context, this study found two types of motives that underlie the act of corruption. First, because motive which is always related to property. This motive does not stand alone but is influenced by previous traditions and behavior that have accustomed acts of corruption. Second, in order to motive which is influenced by one's desire to achieve certain goals, thus encouraging acts of corruption.